2002
DOI: 10.1007/s00464-001-8319-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs open resection of gastric stromal tumors

Abstract: Laparoscopic resection of gastric stromal tumors is safe and appropriate. Tumor size, operating time, and estimated blood loss were equivalent to the open approach, and there was a statistically shorter hospital stay in the laparoscopic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
1
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 27 publications
7
146
1
9
Order By: Relevance
“…During a mean follow-up period (Table 4). 3 showed that laparoscopic resection of gastric stromal tumors was safe and appropriate, and that the laparoscopic group had a shorter hospital stay. Moreover, various laparoscopic approaches for resection of gastric SMTs have been developed, depending on size, location, and transmural characteristics.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…During a mean follow-up period (Table 4). 3 showed that laparoscopic resection of gastric stromal tumors was safe and appropriate, and that the laparoscopic group had a shorter hospital stay. Moreover, various laparoscopic approaches for resection of gastric SMTs have been developed, depending on size, location, and transmural characteristics.…”
Section: Resultsmentioning
confidence: 97%
“…As mentioned, although there have been studies to show the benefits of the laparoscopic wedge approach, they did not have enough patients and did not indicate the size or location of gastric SMTs. 3,11,17 By careful case-matching, we analyzed a total of 100 procedures consisting of 50 LWRs and 50 OWRs. In size-matching, tumors between 2 and 5 cm accounted for the largest proportion (68%), and tumors larger than 5 cm accounted for 12%; the largest diameter in the LWR group was 6 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 3 and 4 summarize several reported series of laparoscopic intragastric resections for GSTs, with the exception of a single case report [7,[9][10][11][12][13][14][15]. The number of cases ranged from 3 to 11, with a mean of 6.7, and the mean patient age was 71 years (range, 65-77 years).…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal is to remove the tumor with tumor free margins since 5-year overall survival in GIST patients with complete gross resection has been estimated at 42% compared to only 9% overall survival if the excision was incomplete [70]. GIST can usually be lifted away from surrounding structures, rarely spread into adjacent organs and therefore offer an excellent opportunity for laparoscopic tumor resection with efficacy and recurrence rates similar or superior to historical open surgical controls [71][72][73][74]. When the tumor attaches to other organs, en bloc resection is appropriate.…”
Section: Role Of Surgerymentioning
confidence: 99%